A critically endangered new species of Croton section Barhamia (Euphorbiaceae) from the Cerrado hotspot, Brazil - Sodré, Rodolfo Carneiro; Pereira, Amanda Da Paixão Noronha; Mendes, Thainara Policarpo; Caruzo, Maria Beatriz Rossi; Silva, Marcos José Da (Phytotaxa, 2025)
A new species of Croton endemic to the Cerrado hotspot (Brazil) is here described and illustrated. Croton rizzoi is assigned to section Barhamia subsect. Medea due to its foliage not viscid, entire leaf margins, pinnate venation, glandular stipules and sepals of pistillate flowers. The new species is most closely related to C. arirambae from the Northern region of Brazil, but differs by having stipules with stipitate-capitate glands with subglobose or ovoid secretory portion, elongate thyrses (up to 11 cm long), anthers 1.4–1.7 mm long, with papillose surface and 2-fid styles. Croton rizzoi has its geographic distributions, morphological relationships, phenology conservation status, and systematic position presented.